Introduction to the thematic issue - Preuveneers, Davy (2012)
This Thematic Issue focuses on software engineering perspectives on the design, the use and the evaluation of Smart Applications for Ambient Intelligence. It congregates works showing the latest advancements in simulated smart environments as well as successful deployments in the real world, with contributions from revised and extended papers from the ISAmI’11 (International Symposium on Ambient Intelligence) event held at the University of Salamanca, Spain in April, 2011. Ambient Intelligence (AmI) is recognized as an established research field where smart and sensitive devices are used as proactive tools to assist people with their day-to-day activities, making everyone’s life more comfortable. The application of software engineering best practices can strengthen the successful development of systems that offer context-aware suggestions or automate tasks according to the current situation of their users. The papers in this Thematic Issue highlight various best practices for engineering intelligent software architectures, with development methodologies for building intelligent applications and case studies on software requirements and testing of smart behavior.